Adaptive Methods for Matching Problem - Hassan, Raid (Iraqi Journal of Science, 2025)
In this paper, we deal with the problem of general matching of two images one of them has experienced geometrical transformations, to find the correspondence between two images. We develop the invariant moments for traditional techniques (moments of inertia) with new approach to enhance the performance for these methods. We test various projections directional moments, to extract the difference between Block Distance Moment (BDM) and evaluate their reliability. Three adaptive strategies are shown for projections directional moments, that are raster (vertical and horizontal) projection, Fan-Bean projection and new projection procedure that is the square projection method. Our paper started with the description of a new algorithm that is low cost ("soft calculation"); the new procedure significantly has improved the Statistical Region Description (SRD). The new method BDM is highly accurate 98% even higher than our previous image matching modified method